Non-Influenza and Non-SARS-CoV-2 Viruses Among Patients with Severe Acute Respiratory Infections in Tanzania: A Post-COVID-19 Pandemic Snapshot - Kelly, Maria Ezekiely; Msafiri, Frank; Averhoff, Francisco; Danda, Jane; Landay, Alan; Simba, Azma; Mwafulango, Ambele Elia; Mosha, Solomoni; Magesa, Alex; Mmbaga, Vida; Chaves, Sandra S. (Viruses, 2025)
Respiratory pathogens are significant causes of morbidity and mortality worldwide. Since the emergence of SARS-CoV-2 in 2019 and the mitigation measures implemented to control the pandemic, other respiratory viruses’ transmission and circulation patterns were substantially disrupted. We leveraged the influenza hospitalization surveillance in Tanzania to understand the distribution of respiratory viruses shortly after nonpharmaceutical interventions (NPIs) were lifted. A total of 475 samples that tested negative for SARS-CoV-2 and influenza from March through May 2022 were included in this study. The samples were tested for 16 virus targets using Anyplex II RV16 multiplex assays. The findings indicate that most hospitalizations (74%) were among children under 15 years, with human bocavirus (HBoV) being the most prevalent (26.8%), followed by rhinovirus (RV, 12.3%), parainfluenza viruses (PIVs1–4, 10.2%), respiratory syncytial virus (RSV, 8.7%), adenovirus (AdV, 4.3%), and metapneumovirus (MPV, 2.9%). Notably, 54% of respiratory hospitalizations had no viruses detected. The findings highlight the broad circulation of respiratory viruses shortly after NPIs were lifted in Tanzania. Surveillance for respiratory pathogens beyond influenza and SARS-CoV-2 can inform public health officials of emerging threats in the country and should be considered an important pandemic preparedness measure at a global level.